Baseline type 2 diabetes had a significant association with elevated high sensitivity cardiac troponin T levels in Chinese community-dwelling population: a 5-year prospective analysis. Issue 1 (December 2017) - Fu, Shihui; Jin, Rongjie; Luo, Leiming; Ye, Ping
Abstract Background The present analysis was designed to investigate the association of type 2 diabetes (T2D) with high sensitivity cardiac troponin T (hs-cTnT) during the 5 years of follow-up, and explore which one of fasting blood glucose (FBG) and postprandial blood glucose (PBG) is a determinant of this association in Chinese community-dwelling population. Methods This prospective community-based analysis was conducted based on 730 participants without coronary artery disease and hs-cTnT values ≥14 pg/mL receiving two measurements of hs-cTnT levels at baseline and follow-up of 5 years. Results Prevalence of T2D was 16.2% (118 participants). Median hs-cTnT levels were 4 (3-7) pg/mL and 6 (5-9) pg/mL at baseline and follow-up, respectively. The variation in hs-cTnT levels had a median of 2 (0-4) pg/ml (p  < 0.001 for variation), and incidence of hs-cTnT levels ≥14 pg/ml was 7.1% (52 participants) at follow-up. T2D had a significant association with elevated hs-cTnT levels in multivariate Logistic regression models (p  < 0.05). Elevated levels of PBG (p  < 0.05) rather than FBG (p  > 0.05) determined the significant association with elevated hs-cTnT levels in multivariate linear regression models. Conclusions This community-based analysis observed that there was a significant increment of hs-cTnT levels, and baseline T2D had a significant association with elevated hs-cTnT levels during the 5 years of follow-up. Moreover, the present analysis demonstrated that PBG rather than FBG played a crucial role in this association in Chinese community-dwelling population without CAD.